A self-powered acceleration sensor with flexible materials based on triboelectric effect. (January 2017) - Xiang, Chenghao; Liu, Chaoran; Hao, Chonglei; Wang, Zuankai; Che, Lufeng; Zhou, Xiaofeng
Abstract: Traditional MEMS acceleration sensors have been well developed, but most of them require an additional power source to operate. Moreover, they are usually susceptible to limited mechanical shock survivability due to the dominant reliance on rigid materials such as silicon. Recently, with the advancement in flexible materials and nanogenerators, piezoelectric sensors have received increasing interests due to the distinctive property of electricity generation, caused by its structural deformation. In this paper, we demonstrate a novel triboelectric acceleration sensor with flexible structure that is not only self-powered without the need of additional power source, but also is durable in a wide spectrum of operating ranges. The sensitivity is measured to be 1.33 mV/(m/s 2 ) with 0.64% nonlinearity over the acceleration range from 0 to 6 m/s 2, and the shock survivability of 15, 000 g. We envision that our work provides a new train of thought to combine MEMS technology and flexible electronics for the development of sensors with high shock survivability and low power consumption. Graphical abstract: Highlights: This sensor presents 1.33 mV/(m/s 2 ) sensitivity and less than 1% nonlinearity. The structure and flexible materials contribute to 15, 000 g shock resistance. Overlapping area among triboelectric layers and electrodes minimizes its volume. Tiny vibration energy can be harvested by this sensor.